Neoplastic disease after acute coronary syndrome: incidence, duration, and features. Issue 10 (October 2018) - Berton, Giuseppe; Cordiano, Rocco; Cavuto, Fiorella; Bagato, Francesco; Segafredo, Beatrice; Pasquinucci, Mattia
Abstract : Aim: To investigate the clinical features and incidence of malignant neoplasia during 17 years of follow-up in an unselected sample of patients with acute coronary syndrome (ACS). Methods: The Adria, Bassano, Conegliano, and Padova Hospital-4 Study on Heart Disease is an ongoing, prospective study of an unbiased population of patients with ACS. Baseline clinical and laboratory data were obtained during the first 7 days of hospitalization at three different intensive coronary care units. The current study included data from 589 patients with ACS. Results: At enrollment, 19 patients had confirmed neoplasia. During follow-up, 99 additional patients developed malignant neoplastic disease. The incidence rate was 17.8 cases per 1000 person-years, which was about three times higher than that observed in the general population. Patients had a shorter duration of neoplasia when they developed it after enrollment compared with those with preexisting neoplasia [hazard ratio = 2.0 (1.5–2.6), P  = 0.001]. Patients with neoplasia who died during follow-up had an earlier onset of neoplasia [hazard ratio = 1.8 (1.1–2.9), P  = 0.01] and shorter duration than survivors [hazard ratio = 4.1 (2.4–7.0), P  < 0.0001]. The estimated time to diagnosis of neoplasia indicated elderly patients had a significantly higher risk than younger people during the 17 years of follow-up. After the onset of neoplasia, survival time declined more sharply in the elderly than younger people. Conclusion: The long-term prospective study showed that patients with ACS have a higher incidence of malignancy than the general population. Those who develop neoplasm after being diagnosed with ACS have a worse prognosis than patients with a preexisting neoplasia.